2008
DOI: 10.1371/journal.pcbi.1000240
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Correlation between Intrahost HIV-1 Quasispecies Evolution and Disease Progression

Abstract: Quantifying the dynamics of intrahost HIV-1 sequence evolution is one means of uncovering information about the interaction between HIV-1 and the host immune system. In the chronic phase of infection, common dynamics of sequence divergence and diversity have been reported. We developed an HIV-1 sequence evolution model that simulated the effects of mutation and fitness of sequence variants. The amount of evolution was described by the distance from the founder strain, and fitness was described by the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 50 publications
2
69
1
Order By: Relevance
“…If this threshold is high, then the titres in the drones also become important and by inference, so does the Varroa infestation status of the drone donor colonies. These different perspectives of the importance of virus titre on the probability of transmission highlight the effect antiviral or anti-Varroa treatments can have on the epidemiology and evolution of a virus (Brunetto et al 2009;Lee et al 2008). The high endophallus DWV infection rate itself suggests that venereal transmission is a major transmission route for DWV Yue et al 2006;, which may in part explain the wide distribution of DWV in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…If this threshold is high, then the titres in the drones also become important and by inference, so does the Varroa infestation status of the drone donor colonies. These different perspectives of the importance of virus titre on the probability of transmission highlight the effect antiviral or anti-Varroa treatments can have on the epidemiology and evolution of a virus (Brunetto et al 2009;Lee et al 2008). The high endophallus DWV infection rate itself suggests that venereal transmission is a major transmission route for DWV Yue et al 2006;, which may in part explain the wide distribution of DWV in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between disease progression and viral evolution has been investigated in detail for HIV-1 (10,19,25,32,35) but to a lesser extent for HIV-2 (20,22). MacNeil et al reported a low evolutionary rate of HIV-2 in chronic infections (22), and Lemey et al reported that the rate of synonymous substitutions was lower for HIV-2 than for HIV-1 in chronic infections (20).…”
mentioning
confidence: 99%
“…It has earlier been revealed that CCR5 and CXCR4, the major co-receptors critical for viral entry into the host cells, are differentially expressed on CD4+ T-cells, and their relative expression is closely associated with disease pathogenesis [18][19][20][21][22][23][24]. We studied their expression on different subsets of T-cells including T-regulatory cells and evaluated their role in changing the frequency of these cells with disease progression.…”
Section: Discussionmentioning
confidence: 99%